2001
DOI: 10.1016/s0960-9822(01)00123-3
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of Xenopus oocyte meiosis arrest by G protein βγ subunits

Abstract: An endogenous G protein betagamma dimer, likely including Xenopus Gbeta1, is responsible for maintaining oocyte meiosis arrest. Resumption of meiosis is induced by Gbetagamma scavengers in vitro or, naturally, by progesterone via a mechanism that suppresses the release of Gbetagamma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
78
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(86 citation statements)
references
References 57 publications
8
78
0
Order By: Relevance
“…Furthermore, since androgens appear to be physiologic mediators of Xenopus laevis oocyte maturation [90], this system serves as an excellent model for studying extranuclear androgen signaling. Using this model system, studies have shown that just as estrogens regulate G protein and kinase signaling in somatic cells, androgen-induced oocyte maturation requires rapid changes in G protein signaling as well as activation of MAPK signaling [75,78,[91][92][93]. Notably, a key regulator of androgen-triggered kinase signaling in oocytes is paxillin because knockdown of its expression abrogates steroid-triggered kinase signaling and downstream maturation [89].…”
Section: Androgenmentioning
confidence: 99%
“…Furthermore, since androgens appear to be physiologic mediators of Xenopus laevis oocyte maturation [90], this system serves as an excellent model for studying extranuclear androgen signaling. Using this model system, studies have shown that just as estrogens regulate G protein and kinase signaling in somatic cells, androgen-induced oocyte maturation requires rapid changes in G protein signaling as well as activation of MAPK signaling [75,78,[91][92][93]. Notably, a key regulator of androgen-triggered kinase signaling in oocytes is paxillin because knockdown of its expression abrogates steroid-triggered kinase signaling and downstream maturation [89].…”
Section: Androgenmentioning
confidence: 99%
“…Evidence supporting this model is plentiful, including the following: First, steroids trigger a rapid decrease in intracellular cAMP with a concomitant decrease in PKA activity [9][10][11][12]. Second, over-expression of either Gα s or Gβγ inhibits steroid-triggered oocyte maturation, while reduction of Gα s or Gβγ levels or activity leads to enhanced maturation in response to steroids [13][14][15][16]. Third, stimulation of overexpressed Gα s -or Gβγ-coupled receptors markedly inhibits steroid-triggered oocyte maturation [17,18].…”
Section: Meiosis In Frog Oocytesmentioning
confidence: 99%
“…[1][2][3]. Progesterone activates the oocyte through a nontranscriptional cytoplasmic signaling pathway that requires one and possibly two types of receptors: XPR1, a conventional transcriptional progesterone receptor that can also initiate cytoplasmic signaling (4,5), and an unidentified G protein-coupled receptor (6)(7)(8). Despite uncertainties about the earliest steps in receptor action, it is well established that progesterone induces two parallel pathways that converge on the activation of cyclin B-cdc2 (Fig.…”
mentioning
confidence: 99%